The Impact of Technology Adoption on Market Structure - Hannan, Timothy H.; McDowell, John M. (The Review of Economics and Statistics, 1990)
This paper examines the impact of bank adoptions of automated teller machines (ATMS) on subsequent levels of concentration in local banking markets. The findings suggest that banks have had some success in using ATMs to attract customers from competitors. As a consequence, technology adoption's impact on market structure depends upon whether it is the larger or smaller firms within the market that adopt the new technology. Large firm adoptions increase concentration levels, while small firm adoptions tend to reduce them. The evidence also suggest that a state of structural disequilibrium seems to be characteristic of banking markets. Copyright 1990 by MIT Press.